Teaching on Jews and Judaism in Selected US Catholic Seminaries - Mazza, George (Studies in Christian-Jewish Relations, 2024)
Interviews with the academic deans or their designees at nine leading Catholic theologates in the US disclosed that there was a serious discrepancy between the formation of Catholic priests and the aspirations of the Second Vatican Council and subsequent official ecclesial teachings on the Catholic Church’s proper relationship with Jews and Judaism. Most of the seminaries had no access to Jewish scholars and had no relationship with the local Jewish community. They also failed to provide any guidance to seminarians on the pastoral care of Catholic-Jewish couples and families, even in dioceses with large Jewish populations. The seminaries, for the most part, were not engaged in promoting Catholic-Jewish scholarship, and they appeared to have no systemic programs on antisemitism or the modern State of Israel. Most significantly, the seminaries provided no homiletic instruction to future priests on addressing the anti-Judaic content in the New Testament, especially during Lent and Holy Week.